2004
DOI: 10.1016/j.icvts.2004.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Giant tracheocele following primary tracheostomy closure in a 3 year old child

Abstract: Tracheocele is a rare pathology, especially complication of tracheal surgery. We present a case of a 3 year old pediatric patient with secondary tracheocele arising after simple surgical closure of tracheostomy. It appeared 2 months after intervention that cervical mass swelling during respiratory acts. Diagnosis was made by TC scan and by dynamic flexible bronchoscope which revealed a substomal segmental tracheomalacia. Surgical procedure consisted of simple excision of tracheocele associated with enhancing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…5 The acquired form can occur secondary to blunt trauma, chronic bronchopulmonary disease, intubation, instrumentation or, in rare cases, tracheostomy, surgical tracheostomy closure, or tracheoesophageal fistula excision. [5][6][7][8] In our patient, the presence of the single, large, airfilled sac with a possible tracheal defect pointed toward the acquired form, but we could not completely rule Tracheocele commonly occurs on the right side. 5 It usually presents as a slowly progressive, large, air-filled swelling in the neck; it may not produce any other symptoms.…”
Section: Discussionmentioning
confidence: 55%
“…5 The acquired form can occur secondary to blunt trauma, chronic bronchopulmonary disease, intubation, instrumentation or, in rare cases, tracheostomy, surgical tracheostomy closure, or tracheoesophageal fistula excision. [5][6][7][8] In our patient, the presence of the single, large, airfilled sac with a possible tracheal defect pointed toward the acquired form, but we could not completely rule Tracheocele commonly occurs on the right side. 5 It usually presents as a slowly progressive, large, air-filled swelling in the neck; it may not produce any other symptoms.…”
Section: Discussionmentioning
confidence: 55%
“…Elevated pressure in the tracheal lumen can be caused by playing wind instruments, glassblowing, positive pressure ventilation and chronic cough. Iatrogenic tracheocele occurring after surgery has also been reported [6,7]. One case of voluminous tracheocele has been described in association with Mounier-Kuhn syndrome [8].…”
Section: Discussionmentioning
confidence: 98%
“…2,[5][6][7][8][9] It has been reported that primary closure with excision of the fistula tract down to the level of the trachea may result in tracheocele, pneumopericardium, pneumothorax, and pneumomediastinum. 1,2,[10][11][12] Closure with a turnover flap of skin and fibroadipose tissue means that the defect in the tracheal lumen is covered by the outer surface of the cutaneous flap. This minimizes the suturing required, and results in fewer problems with insufficiency of the repair.…”
Section: Discussionmentioning
confidence: 99%